The transport and infrastructure conditions of developing the urban environment in the city of Aktobe (Journal of Geography and Environmental Management, 2023)
The rapid expansion of cities presenting the urban environment problems involves the development of transport and infrastructure conditions. To manage the city transport beneficially is possible only taking into consideration the interaction of the population and public transport. Not knowing and disregarding the regional features and principles of such interaction implies difficulties to work out the plan to correctly develop the urban transport, to assess the transport and communications system and transport services. The conditions of the road network and transport infrastructure are considered essential  to enhance the life quality of the urban population and  promote the opportunities for the development of the city's economy.The article presents the analysis of the transport and infrastructure conditions of Aktobe city. The purpose of the study is to review the development of public transport systems in Aktobe and specify their problems. The empirical basis of the study was the data of social surveys held among the residents of the city. The survey involved about 500 people from different districts of the city. The survey results were calculated in points and percentage and then used for the analysis. In the context of permanent development a current big problem for Aktobe is the increase of the part of the population using personal vehicles to move through the city. One of the ways to reduce the negative impact of the transport system on the environment is the development and mainstreamification of the public transport system. The results of the surveys held among the population point to a low level of people’s being ready to refuse from using their own cars and to pass to more ecological transport. According to the opinion of the city residents the quality of the service in public transport has grown over the past 2022-2023. The results of the study can be applied in the work of local self-governments of major cities in the process of implementing transport policy.
Keywords: public transport, transport system, city roads, transport infrastructure, the city of Aktobe.